Monetary and Value Theory: Further Comment - Archibald, G. C.; Lipsey, R. C. (Review of Economic Studies, 1960)
Journal Article A Symposium on Monetary Theory: Monetary and Value Theory: Further Comment Get access G. C. Archibald, G. C. Archibald London Search for other works by this author on: Oxford Academic Google Scholar R. C. Lipsey R. C. Lipsey London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 1, October 1960, Pages 50–56, https://doi.org/10.2307/2296250 Published: 01 October 1960